2000
DOI: 10.1023/a:1008332517333
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of high-dose epirubicin in ovarian cancer patients previously treated with cisplatin

Abstract: It is concluded that HDE is active in platinum-pretreated patients with epithelial ovarian cancer and should be further studied in first-line in combination with paclitaxel and a platinum compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In the 34 patients who had progressed during first-line chemotherapy, the response rate to EPI was 15%; in the 17 patients with persistent disease, it was 12%; and in the 49 patients who relapsed after an initial response, it was 27% (22) . A further subdivision related to the cisplatin-free interval in the 83 patients who progressed before entry into the HDE trial indicated that not only the response rate but also the time to (18,22) 215 0-32 Pegylated liposomal doxorubicin (23) 788 9-31 Idarubicin (18) 47 0 Esorubicin (18) 61 5 Menogaril (18) 51 14 Aclacinomycin (18) 14 0 progression during EPI treatment was strikingly different in patients with a long (>12 months) cisplatin-free interval. In patients who relapsed 6-12 months after the end of first-line chemotherapy, the response to EPI was 20% and the median time to progression was 14 weeks, whereas in those who relapsed beyond 12 months, the response rate was 41% and the median time to progression 25 weeks.…”
Section: Single-agent Anthracycline Therapy In Recurrent Ovarian Cancermentioning
confidence: 96%
See 3 more Smart Citations
“…In the 34 patients who had progressed during first-line chemotherapy, the response rate to EPI was 15%; in the 17 patients with persistent disease, it was 12%; and in the 49 patients who relapsed after an initial response, it was 27% (22) . A further subdivision related to the cisplatin-free interval in the 83 patients who progressed before entry into the HDE trial indicated that not only the response rate but also the time to (18,22) 215 0-32 Pegylated liposomal doxorubicin (23) 788 9-31 Idarubicin (18) 47 0 Esorubicin (18) 61 5 Menogaril (18) 51 14 Aclacinomycin (18) 14 0 progression during EPI treatment was strikingly different in patients with a long (>12 months) cisplatin-free interval. In patients who relapsed 6-12 months after the end of first-line chemotherapy, the response to EPI was 20% and the median time to progression was 14 weeks, whereas in those who relapsed beyond 12 months, the response rate was 41% and the median time to progression 25 weeks.…”
Section: Single-agent Anthracycline Therapy In Recurrent Ovarian Cancermentioning
confidence: 96%
“…In a large phase II study with higher doses of EPI (HDE: 150-180 mg/m 2 , n ¼ 100), in which all patients had received cisplatinbased chemotherapy in first-line, Vermorken et al (22) reported an overall response rate of 20%. In the 34 patients who had progressed during first-line chemotherapy, the response rate to EPI was 15%; in the 17 patients with persistent disease, it was 12%; and in the 49 patients who relapsed after an initial response, it was 27% (22) . A further subdivision related to the cisplatin-free interval in the 83 patients who progressed before entry into the HDE trial indicated that not only the response rate but also the time to (18,22) 215 0-32 Pegylated liposomal doxorubicin (23) 788 9-31 Idarubicin (18) 47 0 Esorubicin (18) 61 5 Menogaril (18) 51 14 Aclacinomycin (18) 14 0 progression during EPI treatment was strikingly different in patients with a long (>12 months) cisplatin-free interval.…”
Section: Single-agent Anthracycline Therapy In Recurrent Ovarian Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…We chose epidoxorubicin for its no cross-resistant activity against drugs received as front-line treatment. Further, epidoxorubicin is a well-known manageable drug, either used alone or in combination regimens as second-line therapy of epithelial ovarian cancer (11) .…”
mentioning
confidence: 99%